Surface Modification of Ti6Al4V Alloy by Pack Boriding - Atar, Erdem; Kayali, E. Sabri; Cimenoglu, Huseyin (Minerals, Metals & Materials Soc, 2009)
In this study, a 10 mu m thick uniform boride layer, composed of TiB2 and TiB phases, was formed on the surface of a Ti6Al4V alloy by pack boriding technique. The hardness of the outer most boride layer was 2700 HV0.025. Beneath the boride layer, a boron diffusion zone (BDZ) appeared with a thickness of about 50 mu m. The microstructure of the BDZ was composed of randomly oriented TiB whiskers dispersed in the matrix of the base metal. In the BDZ, hardness decreased gradually towards the base metal owing to the reduction of the TiB volume fraction. The borided alloy exhibited excellent wear resistance against Al2O3 ball under both unlubricated and lubricated sliding conditions when compared to the as-received state.
138th TMS Annual Meeting and Exhibition -- FEB 15-19, 2009 -- San Francisco, CA
Keywords: boriding; surface treatment; titanium alloy; wear